Development of Life Skills through Football: An Implementation of Character Education - Didin Khoirudin Yusuf; Ribut Wahidi; Oman Hadiana; Boby Agustan (Indonesian Journal of Sport Management, 2024)
This research is based on the condition of football players in Indonesia who still have minimal attitude in terms of respect. Players often act unsportsmanlike, such as trying to injure opponents, not shaking hands after committing a violation, and protesting excessively to the referee.  This study aims to develop a soccer training model based on character education in order to improve life skills.  The pretest results of the life skills of SSB Putra Karamat students using the character education development model seen based on the aspects of emotional skills, problem solving and decision making, leadership, and respect showed a significant difference with the pretest results of the life skills of SSB Tesa students. Likewise, the posttest results of the life skills of SSB Putra Karamat students differed from SSB Tesa students in measuring the same aspects during the pretest, where the life skills of SSB Putra Karamat students looked better. The implementation of character education (tolerance, discipline, responsibility, and respect) in the soccer training program has a positive impact on the life skills of players. Players can better control their emotions during the match, players can solve problems and make the right decisions, have a leadership spirit, and have a respectful attitude towards other players, referees, officials, and everyone involved in the soccer game. The impact of implementing the character education model in football games provides new innovations to the development of sports education science. Football players need to be equipped with good characters, not only having good basic techniques, prime physical condition, and good playing tactics.